Worsening of asthma control after COVID-19 - Agondi, Rosana Câmara; Menechino, Natália; Marinho, Ana Karolina Barreto Berselli; Kalil, Jorge; Giavina-Bianchi, Pedro (Frontiers in Medicine, 2022)
Background: SARS-CoV-2 enters lung cells via angiotensin-converting enzyme 2 (ACE2) receptor. Several studies suggest that interleukin-13, an important cytokine involved in T2 inflammation, reduces ACE2 expression, and therefore, asthma would not be a significant risk factor for the development of severe COVID-19. However, several asthma-related risk factors should be valued during the concurrent occurrence of asthma and COVID-19. The purpose of this study was to compare the evolution of asthma in patients who had COVID-19 with those who did not have the disease. Methods: This was an observational and retrospective study involving asthmatic patients followed up at a tertiary center. Patients were assessed for severity of asthma, atopy, comorbidities, and COVID-19. Worsening of asthma was considered when, during the period of Sept 2020 to Oct 2021, patients referred an increasing of asthma symptoms and a need to increment their maintenance therapy. Results: This study included 208 asthmatic patients, the mean age was 52.75 years, 79.81% were atopic asthmatics, and 59 (28.37%) had laboratory-confirmed coronavirus disease. Of all patients infected with the SARS-CoV-2, eleven (18.64%) needed hospitalization and required oxygen supply with an O2 mask. Comparing the worsening of asthma between patients who had COVID-19 and those who had not the disease, there was a statistically significant difference, 33.90% vs 11.41%, respectively (p<.001). There was no statistical significance regarding asthma comorbidities. Conclusion: This study assessed a group of asthmatic patients that had COVID-19, and that although the respiratory symptoms related to COVID-19 were mild to moderate, a subgroup of these asthmatic patients evolved with a chronic worsening of their asthma requiring an increment in asthma medication to control the disease.